The Nature and Significance of the Carthage-Colton Shear Zone and Related Late-to-Postectonic Granites and Ore Deposits; Adirondack Mountains, New York - Johnson, E; Selleck , B.; DeLorraine, W.; M. V. Lupulescu (2005)
Keywords: geology

Response to Revilla, and Buckley and Ruxton: The Resource Dispersion Hypothesis - Johnson, D.; MacDonald, D.; R. W. Kays; Blackwell, P. G. (Trends in Ecology and Evolution, 2003)
We agree with Revilla [1] that the resource dispersion hypothesis (RDH) indeed lacks comprehensive evidence in any one specific case; however, this deficiency results from a lack of good tests, rather than from the failure of any tests [2]. Revilla's claim that ‘we only need evidence against one of its assumptions and/or predictions to invalidate it’, is too sweeping. RDH cannot be rejected just because it does not work everywhere or is difficult to test. Ecological models can only be refined into theories by discovering where they do not work, as well as where they do [3]. The costs of group living that Revilla cites do not detract from the proposition that heterogeneous resources will lower those costs compared with homogenous resources. Revilla sees a ‘conceptual gap’ between the RDH mechanism and a causal means of group formation because he incorrectly assumes that wherever resources are heterogeneous, RDH automatically predicts animals to live in groups. RDH was always a facilitating, rather than a causal, factor leading to group formation 4 and 5. We agree that ‘resource patchiness alone’ is not enough to explain group living (indeed, we have previously outlined why simultaneous dispersal costs are crucial 6 and 7) – RDH is not exclusive of other theories.
Keywords: resource dispersion hypothesis

Does the resource dispersion hypothesis explain group living? - Johnson, D. D. P.; R. W. Kays; Blackwell, P. G.; MacDonald, D. W. (Trends in Ecology and Evolution, 2002)
The resource dispersion hypothesis (RDH) asserts that, if resources are heterogeneous in space or time, group living might be less costly than was previously thought, regardless of whether individuals gain direct benefits from group membership. The RDH was first proposed more than 20 years ago and has since accumulated considerable support. However, it is sometimes discredited because a priori tests of specific predictions are few, relevant variables have proved difficult to define and measure, and because its assumptions and predictions remain unclear. This is unfortunate because the RDH provides a potentially powerful model of grouping behavior in a diversity of conditions. Moreover, it can be generalized to predict other phenomena, including spacing behavior in nonsocial animals and utilization of resources other than food. Here, we review the empirical support, clarify the predictions of the RDH and argue that they can be used to provide better tests.
Keywords: Foraging; Group living; Group size; Heterogeneity; Patches; resource dispersion hypothesis; Resources; Social organisation; Sociality; Territoriality

Preface - Johnson, M. E.; E. Landing (Silurian Cycles: Linkages of Dynamic Stratigraphy with Atmospheric, Oceanic, and Tectonic Changes, 1998)
Keywords: geology

Radiocabon Dates on Bones of Extinct Birds from Hawaii - James, H. F.; T. W. Stafford Jr.; D. W. Steadman; Olson, S. L.; Martin, P. S.; Jull, A. J. T.; McCoy, P. C. (Proceedings of the National Academy of Sciences, 1987)
Bones from a stratified sedimentary deposit in the Puu Naio Cave site on Maui, Hawaiian Islands, reveal the late Holocene extinction of 19 species of birds. The age of the sediment and associated fauna was determined by direct radiocarbon dating (tandem particle accelerator-mass spectrometer; TAMS) of amino acids extracted from bones weighing as little as 450 mg. The 14C dates indicate that sediment has been accumulating in the lava tube for at least the last 7750 years, a suitable time frame for testing the hypothesis that Holocene extinction on islands began after human colonization. Despite growing evidence that a worldwide wave of extinctions coincided with human colonization of oceanic islands, little radiometric data have been available to date the extinction of most small fossil vertebrates on islands. The TAMS technique of dating purified collagen from the bones of small vertebrates could lead to vastly improved chronologies of extinction for oceanic islands where catastrophic mid- to late-Holocene extinction is expected or known to have occurred. Chronologies derived from nonarcheological sites that show continuous sedimentation, such as the Puu Naio Cave deposit, may also yield key evidence on the timing of earliest human settlement of Oceania.
Keywords: biology paleontology

Paleoecology of a Fossil Plant Assemblage from a pre-Wisconsinan Till in Southern Illinois - Jackson, S. T.; N. G. Miller (The American Midland Naturalist, 1983)
Macrofossils and pollen have been recovered from a glacial till in Jackson Co., Illinois, assigned to the Early Illinoian Liman Substage. The assemblage is dominated by bryophyte and vascular plant taxa of boreal and boreal-temperate distributions. A few taxa of temperate distribution are also present. The boreal elements are evidently from a glacial period (presumably the Early Illinoian); it is not entirely clear whether the other members of the flora are contemporaneous with the boreal plants or are redeposited from interglacial sediments. Overall, the assemblage is ecologically consistent, and is similar to Late Wisconsinan macrofossil floras in eastern and central North America. Habitats and communities indicated by the assemblage include hardwater lake, calcareous wetland and spruce-fir-tamarack forest or woodland.
Keywords: biology paleontology

Recent Developments in Control of Blackflies - H. Jamnback (Annual Review of Entomology, 1973)
Keywords: biology

Aerial Application Of Larvicides For Control Of Simulium damnosum In Ghana: A Preliminary Trial - H. Jamnback; Duflo, T.; Marr, D. (Bulletin of the World Health Organization, 1970)
Keywords: biology

Bloodsucking Flies and Other Outdoor Nuisance Arthropods of New York State - H. Jamnback (New York State Museum Memoir, 1969)
Keywords: biology

Field Tests with Larvicides Other than DDT for Control of Blackfly (Diptera: simuliidae) in New York - H. Jamnback (Bulletin of the World Health Organization, 1969)
Keywords: biology

Some Effects of Ingested Thiotepa on the Development of Plasmodium gallinaceum in Yellow-fever Mosquitoes and in Chicks - H. Jamnback (Journal of Economic Entomology, 1967)
In feeding tests, 1.0% thiotepa (tris (1-aziridinyl) phosphine sulfide) in 5% sucrose solution was rapidly lethal to most females of the yellow-fever mosquito, Aedes aegypti (L.). At this concentration it was calculated that approximately 4600 mg of thiotepa per kg of mosquito weight was ingested. The mortality of mosquitoes feeding on 0.1% thiotepa was 69% on day 20, 17 days after exposure, as compared with 23% in untreated mosquitoes. With 0.1% thiotepa, there was a significant reduction in the size of oocysts and obvious abnormalities in their appearance, but there was no significant difference between the numbers of oocysts in treated and untreated mosquitoes. Sporozoite production was delayed but not entirely prevented; the length of the extrinsic period being almost doubled. Dissections made on day 20 or thereafter indicate that the sporozoite rate was reduced by 68%. Transmission to chicks by thiotepa-treated mosquitoes (on day 20) was reduced by 88%. Plasmodium gallinaceum Brumpt in the 2 chicks infected by thiotepa-treated mosquitoes was infective to other mosquitoes and developed normally in them. The effects of lower concentrations of thiotepa were studied in less detail. Sporozoite rates were reduced and the appearance of sporozoites was delayed in mosquitoes that fed on 0.01% thiotepa but were unaffected in mosquitoes that fed on 0.001% thiotepa.
Keywords: biology

Testing Blackfly Larvicides in the Laboratory and in Streams - H. Jamnback; Frempong-Boadu, J. (Bulletin of the World Health Organization, 1966)
Keywords: biology

The Culicoides of New York (Diptera: Ceratopogonidae) - H. Jamnback (New York State Museum Bulletin, 1965)
Keywords: biology

A Review of Arbovirus Surveillance on Long Island. 1959-1965 - H. Jamnback; Berg, E.; Whitney, E. (proceedings of the New Jersey Mosquito Extermination Association, 1965)
Keywords: biology

Further Observation on the Effectiveness of Chemically Treated Screens in Killing Biting Midges, Culicoides sanguisuga (Diptera:Ceratopgonidae) - H. Jamnback (Journal of Economic Entomology, 1963)
Keywords: biology

The Species of Culicoides Related to obsoletus (Maigen) in Eastern North America (Diptera:Ceratopogonidae) - H. Jamnback; Wirth, W. W. (Annals of the Entomological Society of America, 1963)
The obsoletus group of the subgenus Culicoides (Avaritia) is characterized and the four eastern North American species, which were previously included under the names obsoletus (Meigen) and chiopterus (Meigen), are described with keys for identification of males and females, and when known, the larvae and pupae. These four species are alachua n. sp. from Florida; chiopterus (Meigen) not abundant, probably widespread; obsoletus (Meigen) common and widespread; and sanguisuga (Coquillett), the important pest of eastern woodlands. The known distribution and breeding habitats of these species are discussed.
Keywords: biology

Studies of Populations of Adult and Immature Culicoides sanguisuga (Diptera:Ceratopogonidae) - H. Jamnback; Watthews, T. (Annals of the Entomological Society of America, 1963)
The method used in making landing-rate counts of Culicoides sanguisuga (Coquillett), an abundant pest of man in the Adirondacks, is described. Landing rates were low initially at a given site, and increased to a peak 10 to 12 minutes later. Counts were highest about an hour after sunrise and at sunset. In open meadows the counts generally declined to zero during the day between the morning and evening peaks. In moist, shaded sites, protected from the wind, landing rates diminished but punkies continued to be annoying during the middle of the clay. It is suggested that the rate of moisture loss is an important factor influencing the activity of the punkie, and a close relationship between the evaporation rate and landing rate is demonstrated. Seasonal changes in populations of C. sanguisuga, as indicated by landingrate counts and light-trap collections, were comparable. The first females appeared in late May. Populations then increased rapidly and reached peak numbers in late June and early July. The numbers diminished slowly thereafter and punkies were found only in small numbers after mid-August, although occasional specimens were present into October. C. sanguisuga overwinters in the larval stage. In 1961, larval populations were high in early May, then declined during the period of pupation from late May into early June. Numbers increased thereafter owing to the appearance of recently hatched small larvae. Prepupation population levels were reached by late July.
Keywords: biology

Effects of DDT As Used in Blackfly Larval Control, On Stream Arthropods - H. Jamnback; Eabry, H. H. (Journal of Economic Entomology, 1962)
A study of the possible cumulative effects of DDT on arthropods in streams treated for black fly larval control for 5 to 10 years was carried out in 1961. Statistical analysis based on 348 square-foot riffle samples taken in treated and untreated Adirondack Mountain streams indicates that a significantly smaller number of Ephemeroptera and Diptera were present in the regularly treated streams than in those untreated, and that the reduction in overall numbers of arthropods approached hut did not reach a significant level. The numbers of arthropods in 11 regularly treated streams sampled in 1950-52 and again in 1961 were about the same during the two sampling periods. The ratio of weight to volume to numbers of arthropods was about the same in regularly treated, irregularly treated, and untreated streams sampled in 1961.
Keywords: biology

An Electric Method of Testing the Effectiveness of Chemicals in Killing Backfly Larvae (Simuliidae: Diptera) - H. Jamnback (Mosquito News, 1962)
Keywords: biology

Culiseta melenara (coq.) Breeding on Long Island, New York - H. Jamnback (Mosquito News, 1961)
Keywords: biology

The Effectiveness of Chemically Treated Screens in Killing Annoying Punkies, Culicoides obsoletus - H. Jamnback (Journal of Economic Entomology, 1961)
A method of testing and evaluating chemicals painted on window screens for control of punkies (Culicoules obsoletus (Meigen)) in dwellings consisted of using test chambers made from small cartons with one end covered by transparent plastic and the other end opaque. A screen was placed in the chamber between the light and dark ends. When the adults were introduced into the chamber at the dark end they quickly migrated to the light end passing through the treated screens. A 7.7% marathon-alcohol solution painted on screens killed Culicoides adults that had passed through them in less than an hour while a 10% DDT-oil solution required several hours before an appreciable mortality occurred. The malathion-painted screens were still highly effective in killing exposed punkies 21 days after treatment.
Keywords: biology

Observations on Culicoides obsoletus (Meigen) in the Laboratory (Diptera:Ceratopgonidae) - H. Jamnback (Mosquito News, 1961)
Keywords: biology

The Common Salt-Marsh Tabanidae of Long Island, New York - H. Jamnback; Wall, W. (New York State Museum Bulletin, 1959)
Keywords: biology

Control of Culicoides mellus (Coq.) (Diptera: Heleidae) in Small Plots, With Brief Descriptions of the Larvae and Pupae of Two Coastal Culicoides - H. Jamnback (Mosquito News, 1958)
Keywords: biology

A Sampling Procedure for Culicoides melleus (Coq.) (Diptera:Heleidae) with Observations on the Life Histories of Two Coastal Culicoides - H. Jamnback; Wall, W. J.; Collins, D. L. (Mosquito News, 1958)
Keywords: biology

Control of Salt-Marsh Tabanuus Larvae with Granulated Insecticides - H. Jamnback; Wall, W. J. (Journal of Economic Entomology, 1957)
Experiments on the control of larvae of Tabanus spp. in salt marshes with granular formulations of insecticide were made on Long Island, New York, in 1955 and 1956. In 1955, granules of Attaclay or Diluex impregnated with dieldrin, aldrin, chlordane, heptachlor or DDT were applied by hand to 60-ft. square plots in salt marshes having high and relatively uniform populations of Tabanus larvae. Granules were used because they readily penetrate the dense marsh vegetation. Results were evaluated by a method in which the larvae are brought to the surface of cleared areas by the use of a pyrethrum spray [see next abstract]. Dieldrin was applied at dosages of 0.09-2.5 lb. per acre and was the most effective of the insecticides tested [cf. R.A.E., B 45 116]. No larvae could be found in plots treated with the higher dosages (0.6 Ib. or more) after ten days, or in any of the plots after 32 days, when control plots yielded 14.9 larvae per sq. yard. DDT was the least effective insecticide, giving poor control in 28 days at 2 Ib. per acre. The addition of 5 per cent. urea as a stabiliser to granules of 30/40 mesh Attaclay with 2.5 per cent. dieldrin, which was tried in 1956. did not appear to influence effectiveness.
Keywords: biology

First Record of Simulium (Eusimulium) congareenarum (D. & S.) from New York, with Descriptions of the Male, Female, Pupa and Larva - H. Jamnback (Annals of the Entomological Society of America, 1957)
Twenty-three species of black flies have been recorded from New York State (Stone and Jamnback, 1955). In 1955 a hitherto unrecorded species was collected on Long Island, increasing the number to twenty-four. A redescription of the female and first descriptions of the male, pupa and larva of this species are presented below. The characters used in the descriptions are discussed in the publication cited above.
Keywords: biology

The Control of Black Flies (Diptera: Simuliidae) in New York - H. Jamnback; Collins, D. L. (New York State Museum Bulletin, 1955)
Keywords: biology